Riwayat Kunjungan Antenatal Care (ANC) dan Pemberian MP-ASI Kaitannya dengan Kejadian Stunting - Ni Ketut Kariani; Riski Riski (Jurnal Ners, 2025)
The World Health Organization (WHO) declared the estimated of stunting prevalence in 2020 about 22%, in Indonesia have the prevalence of stunting in 2021 in Indonesia will be 24.4% and about 29.7% in Central Sulawesi, and Sigi Regency has the highest prevalence of stunting about 40.7%. And among the nineteen sub-districts in Sigi Regency in 2021, Kinovaro Subdistrict was in the second rank of stunting cases of 269 children under five, and this has increased over the past two years. The aim of the research was to analyze the correlation between the history of Antenatal Care (ANC) visiting the providing of complementary food with stunting case. The research method uses a case-control design. The total population was toddlers aged 24-59 months and the total sample was divided into 37 cases and 37 controls that were taken by purposive sampling technique. The results of the Mann-Whitney test analysis, based on women's characteristics (age, education, and occupation) found significant differences (p-value ≤0.05) between the case and control groups and the characteristics of children under five (gender and age) there were no significant differences (p-value > 0.05) between the two groups. The results of the chi-square test found a significant relationship with (p-value ≤0.05) history of Antenatal Care (ANC) visits and providing of complementary foods to stunting cases. The conclusion of the research mentioned that the history of Antenatal Care (ANC) visits and providing of complementary foods have a correlation with stunting cases. Suggestions for health workers, especially nutritionists should more active in conducting counseling regarding toddler nutrition to prevent stunting cases and for women should be more active in participating in posyandu and other health education activities as well.